Method for preparing porous hydrothermal carbon material from waste plastics and application of porous hydrothermal carbon material

By mixing waste plastic with water and organic solvent in a closed container and using an inorganic alkali catalyst to perform hydrothermal carbonization treatment under ultrasonic, the problem of complex and environmental pollution of waste plastics in the prior art is solved, efficient conversion into porous hydrothermal carbon materials is achieved, and excellent photocatalytic and adsorption properties are demonstrated.

CN119612483APending Publication Date: 2025-03-14NORTHWEST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411706647.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively deal with waste plastic, which leads to environmental pollution, and the process of converting plastic into high-value-added porous hydrothermal carbon materials is complicated, and it is accompanied by by-product generation, which is not conducive to product separation.

Method used

The waste plastic is mixed with water and water-insoluble organic solvent in a closed container, and an inorganic alkali catalyst is added to form an organic-water emulsion system with ultrasonic assistance. After hydrothermal carbonization treatment, porous hydrothermal carbon material is obtained.

Benefits of technology

It realizes pollution-free and easy conversion of waste plastic into porous hydrothermal carbon materials. The material exhibits excellent photocatalytic and adsorption properties, with greater economic value and social significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612483A_ABST
    Figure CN119612483A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a porous hydrothermal carbon material by using waste plastics, which comprises the following steps: dispersing the waste plastics in an organic solvent and water in a closed container, adding a water-insoluble solid base catalyst, and forming an organic-water emulsion system under the assistance of ultrasonic waves; and then, carrying out hydrothermal treatment at the temperature of 160-280 DEG C, soaking and washing a solid phase obtained by separation with diluted hydrochloric acid, and drying to obtain the porous hydrothermal carbon material. The preparation process is simple and convenient, conditions are easy to control, the waste plastic is converted into the hydrothermal carbon material with application value and high additional value, and the hydrothermal carbon material has good application in the aspects of photocatalysis and heavy metal ion adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a porous hydrothermal carbon material by utilizing waste plastics and application thereof, belonging to the technical field of organic waste resource recycling. Background Art

[0002] As an important basic material, plastics have been widely used in all aspects of the economy and society. While bringing many conveniences to people's production and life, they also bring huge environmental challenges. Polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC) and polyethylene terephthalate (PET) are the main components of plastic waste in urban solid waste. Plastic waste accounts for about 8% of the total weight of urban solid waste and about 18% of the volume. The amount of plastic waste is increasing around the world. Therefore, it is of great significance to upgrade mixed plastic waste into high value-added products.

[0003] Guangqiang Xu studied the selective conversion of commercial plastics and mixed plastics into high-value-added chemicals or original monomers through a "one-pot" depolymerization method driven by Zn(HMDS)2 (ACS Sustainable Chemistry & Engineering, 2022, 10, 30, 9860-9871). Xuecheng Chen used calcination and etching to produce hierarchical porous carbon with high specific surface area from waste polyethylene terephthalate porous carbon materials (Science of The Total Environment 2020, 723, 138055). Martin studied the co-depolymerization of polyvinyl chloride and polyethylene terephthalate into terephthalic acid and 1,2-dichloroethane (Nature Sustainability 2023, 6, 1685-1692). However, the above process is complicated and accompanied by the generation of by-products, which is not conducive to product separation.

[0004] Therefore, it is urgent to develop a pollution-free, simple, and efficient method for treating waste plastics and waste mixed plastics. Converting solid waste plastics and their mixtures into high-value-added porous hydrothermal carbon materials will have greater economic value and social significance. Summary of the invention

[0005] In view of the problems of difficulty in recycling waste plastics and environmental pollution, the present invention provides a method and application of preparing porous hydrothermal carbon material by using waste plastics.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing porous hydrothermal carbon materials using waste plastics: in a closed container, waste plastics are added to a water-immiscible organic solvent and water, and an inorganic base catalyst that is insoluble in water or slightly soluble in water is added to form an organic-water emulsion system under the assistance of ultrasound, and then a porous carbon material is obtained by hydrothermal carbonization. Furthermore, the solid phase species after the reaction are separated and subjected to 0.01 mol∙L -1 After washing three times with hydrochloric acid, three times with water and three times with ethanol, it was dried at 80-120℃ for 4-24 h.

[0007] The above-mentioned waste plastics are selected from polyethylene terephthalate (PET), polypropylene (PP), polyethylene (PE), polyvinyl chloride (PVC), polyurethane (PU), and polystyrene (PS).

[0008] The water-immiscible organic solvent is selected from cyclohexane, octane, heptane, petroleum ether, toluene, p-xylene, m-xylene, o-xylene, biphenyl, and cyclohexanone. In the organic solvent-water system, the volume ratio of the organic solvent to water is M , M The range is 10~500. The volume ratio of waste plastic mass to organic solvent-water is R , R The range is 0.005~0.5g / mL.

[0009] The inorganic base catalyst is selected from Mg(OH)2, Ca(OH)2, Ba(OH)2, Sr(OH)2, CaO, MgO, BaO, SrO. The mass ratio of the inorganic base catalyst to the waste plastic is C , C The range is 0.01~1.

[0010] In the above preparation method, an organic solvent-water system containing waste plastics is ultrasonically assisted to form an emulsion, the ultrasonic power is 200~1800 W, and the ultrasonic time is 30~240 min.

[0011] In the above preparation method, the hydrothermal treatment reaction temperature is 160~280℃, and the reaction time is 6~120h.

[0012] The porous hydrothermal carbon material prepared by the above method. The porous hydrothermal carbon material can be used in the photocatalytic reduction of oxygen to prepare hydrogen peroxide, or the decomposition of hydrogen from water, or the reduction of carbon dioxide to prepare carbon monoxide, or the adsorption of heavy metal ions. The photocatalytic reaction is carried out in deionized water, and the catalyst can be suspended in the reaction system, or it can be applied to a carrier that does not absorb visible light and ultraviolet light (such as a quartz sheet). The photocatalytic reaction can be carried out in a quartz tube or in a fixed bed reactor. The reaction gas enters the device by bubbling, or is carried out in the reactor in the form of a gas-liquid two-phase mixture. The photocatalytic reaction is carried out in the ultraviolet visible light range, and the light source includes sunlight or an artificial light source (such as a xenon lamp, LED, tungsten lamp, mercury lamp, etc.).

[0013] The adsorption experiment is carried out in a prepared solution containing heavy metal ions, the adsorbent is suspended in the reaction system and stirred. The removal efficiency of heavy metals is quantified by measuring the adsorption amount under a certain contact time.

[0014] The present invention aims at the environmental pollution caused by the landfill and incineration of waste plastics, and develops a method for hydrothermal treatment of waste plastics using an organic-water emulsion system. Compared with the prior art, the present invention has the following advantages: (1) an inorganic base insoluble in water is used to promote the formation of the organic-water emulsion system, and catalyzes the conversion of waste plastics into porous carbon materials during the hydrothermal treatment process; (2) the obtained solid porous carbon material is used as a catalyst and adsorbent, and exhibits excellent photocatalytic and adsorption properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a physical comparison diagram of the microwave-assisted organic-water emulsion system of Example 1 of the present invention and the non-microwave-assisted system of Example 4; Figure 2 TEM image of Example 1 of the present invention; Figure 3 This is the TEM image of Example 5 of the present invention. DETAILED DESCRIPTION

[0016] Below in conjunction with specific embodiment of the present invention, technical scheme of the present invention is clearly and completely described, it is obvious that described embodiment is only a part of embodiment of the present invention, rather than whole embodiment. The reagent, method and equipment adopted in the present invention are conventional reagents, methods and equipment in the art. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of the present invention. Example 1

[0017] 1.1 g of waste PVC was dispersed in 20 mL of cyclohexane and 2 mL of deionized water, and 0.5 g of Mg(OH)2 was added. The dispersed solution was ultrasonicated at 200 W for 240 min and then transferred to a closed reactor and heated at 5 °C min -1 The temperature was raised to 280°C and stirred at this temperature for 6 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing with hydrochloric acid three times, washing with water and ethanol three times each, and drying at 80 °C for 24 h. The transmission electron micrograph shows that it has a porous structure ( Figure 2 ). Example 2

[0018] This example is a comparative example of Example 1, except that no organic solvent is added. Specifically, 1.1 g of waste PVC was dispersed in 22 mL of deionized water, and 0.5 g of Mg(OH)2 was added. The dispersed solution was ultrasonicated at an ultrasonic power of 200 W for 240 min and then transferred to a closed reactor and heated at 5 °C min -1 The temperature was raised to 280°C and stirred at this temperature for 6 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The sample was washed by immersion in hydrochloric acid for three times, washed with water and ethanol for three times each, and dried at 80°C for 24 h to obtain a hydrothermal carbon material. Example 3

[0019] This example is a comparative example of Example 1, except that deionized water is not added. Specifically, 1.1 g of waste PVC was dispersed in 22 mL of cyclohexane, and 0.5 g of Mg(OH)2 was added. The dispersed solution was ultrasonicated at 200 W for 240 min and then transferred to a closed reactor and heated at 5 °C min -1 The temperature was raised to 280°C and stirred at this temperature for 6 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The sample was washed by immersion in hydrochloric acid for three times, washed with water and ethanol for three times each, and dried at 80°C for 24 h to obtain a hydrothermal carbon material. Example 4

[0020] This example is a comparative example of Example 1, except that no organic-water emulsion system is formed (no ultrasonic treatment is performed). Specifically, 1.1 g of waste PVC is dispersed in 20 mL of cyclohexane and 2 mL of deionized water, and 0.5 g of Mg(OH)2 is added. The dispersed solution is transferred to a closed reactor and heated at 5°C min -1The temperature was raised to 280°C and stirred at this temperature for 6 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The sample was washed by immersion in hydrochloric acid for three times, washed with water and ethanol for three times each, and dried at 80°C for 24 h to obtain a hydrothermal carbon material. Example 5

[0021] This example is a comparative example of Example 1, except that no base catalyst is added. Specifically, 1.1 g of waste PVC is dispersed in 20 mL of cyclohexane and 2 mL of deionized water. The dispersed solution is ultrasonicated at 200 W for 240 min and then transferred to a closed reactor and heated at 5 °C min -1 The temperature was raised to 280°C and stirred at this temperature for 6 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The hydrothermal carbon material was obtained by immersion washing with hydrochloric acid three times, washing with water and ethanol three times each, and drying at 80°C for 24 h. The transmission electron micrograph shows that the porosity of the hydrothermal carbon material is significantly reduced ( Figure 3 ). Example 6

[0022] 13 g of waste PVC and 12.5 g of waste PET mixed material were dispersed in 50 mL of p-xylene and 1 mL of deionized water, and 0.255 g of CaO was added. The dispersed solution was ultrasonicated at 500 W for 180 min and then transferred to a closed reactor and heated at 1 °C min -1 The temperature was raised to 160 °C and stirred at this temperature for 120 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing in hydrochloric acid for three times, washing with water and ethanol for three times each, and drying at 120°C for 4 h. Example 7

[0023] 0.25 g of waste PE was dispersed in 50 mL of octane and 0.5 mL of deionized water, and 0.25 g of Ca(OH)2 was added. The dispersed solution was ultrasonicated at 1000 W for 120 min and then transferred to a closed reactor and heated at 15 °C min -1 The temperature was raised to 190 °C and stirred at this temperature for 96 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing in hydrochloric acid for three times, washing with water and ethanol for three times each, and drying at 90°C for 20 h. Example 8

[0024] 3.5 g of waste PVC, 2.5 g of waste PET, 3.0 g of waste PE and 1.05 g of waste PP were dispersed in 100 mL of petroleum ether and 0.5 mL of deionized water, and 0.5025 g of CsO was added. The dispersed solution was ultrasonicated at an ultrasonic power of 1800 W for 30 min and then transferred to a closed reactor and heated at 20 °C min -1 The temperature was raised to 220 °C and stirred at this temperature for 11 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing in hydrochloric acid for three times, washing with water and ethanol for three times each, and drying at 100°C for 16 h. Example 9

[0025] 0.4 g of waste PVC, 0.3 g of waste PET, 0.4 g of waste PE, 0.6 g of waste PP and 0.3 g of waste PS were dispersed in 90 mL of heptane and 0.3 mL of deionized water, and 0.2 g of Ba(OH)2 was added. The dispersed solution was ultrasonicated at an ultrasonic power of 1500 W for 60 min and then transferred to a closed reactor and heated at 8 °C min -1 The temperature was raised to 240 °C and stirred at this temperature for 24 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing in hydrochloric acid for three times, washing with water and ethanol for three times each, and drying at 115°C for 14 h. Example 10

[0026] 3.0 g of waste PVC, 2.0 g of waste PET, 1.5 g of waste PE, 2.5 g of waste PP and 1.0 g of waste PS were dispersed in 120 mL of toluene and 0.3 mL of deionized water, and 3.0 g of MgO was added. The dispersed solution was ultrasonicated at an ultrasonic power of 1300 W for 120 min and then transferred to a closed reactor and heated at 12 °C min -1 The temperature was raised to 260 °C and stirred at this temperature for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing in hydrochloric acid for three times, washing with water and ethanol for three times each, and drying at 85°C for 22 h. Embodiment 11

[0027] 3.15 g of waste PVC and 3.1 g of waste PE mixed materials were dispersed in 100 mL of cyclohexanone and 0.2 mL of deionized water, and 0.5 g of Ba(OH)2 was added. The dispersed solution was ultrasonicated at 900 W for 150 min and then transferred to a closed reactor and heated at 10 °C min -1 The temperature was raised to 170 °C and stirred at this temperature for 40 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing in hydrochloric acid for three times, washing with water and ethanol for three times each, and drying at 95°C for 14 h. Example 12

[0028] 2.0 g of waste PE, 1.4 g of waste PP and 1.6 g of waste PS were dispersed in 120 mL of m-xylene and 1 mL of deionized water, and 2.0 g of Ba(OH)2 and 2.0 g of BaO were added. The dispersed solution was ultrasonicated at 700 W for 200 min and then transferred to a closed reactor and heated at 4 °C min -1 The temperature was raised to 200 °C and stirred at this temperature for 12 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing with hydrochloric acid three times, washing with water and ethanol three times each, and drying at 105°C for 13 h. Example 13

[0029] 1.08 g of waste PET and 0.92 g of waste PS mixed material were dispersed in 80 mL of toluene and 1 mL of deionized water, and 0.4 g of Mg(OH)2 was added. The dispersed solution was ultrasonicated at 300 W for 220 min and then transferred to a closed reactor and heated at 2 °C min -1 The temperature was raised to 270 °C and stirred at this temperature for 8 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing with hydrochloric acid three times, washing with water and ethanol three times each, and drying at 115°C for 10 h. Embodiment 14

[0030] 3.5 g of waste PET, 2.5 g of waste PE and 0.5 g of waste PS were dispersed in 125 mL of biphenyl and 0.5 mL of deionized water, and 1.5 g of Sr(OH)2 was added. The dispersed solution was ultrasonicated at an ultrasonic power of 1700 W for 45 min and then transferred to a closed reactor and heated at 14 °C min-1 The temperature was raised to 255°C and stirred at this temperature for 13 h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid was separated by centrifugation. -1 The porous hydrothermal carbon material was obtained by immersion washing in hydrochloric acid for three times, washing with water and ethanol for three times each, and drying at 112°C for 11 h. Embodiment 15

[0031] 25 mg of the solid product in Examples 1 to 14 was added to a quartz tube containing 50 mL of deionized water, and oxygen was continuously introduced to exhaust the gas in the reactor, and a 300 W LED lamp was turned on, and the mixture was fully stirred for 1 h under illumination. After the reaction was completed, the concentration of hydrogen peroxide in the liquid was measured.

[0032] Example 16

[0033] 50 mg of the solid product in Examples 1 to 14 was added to a quartz tube containing 90 mL of deionized water and 10 mL of triethanolamine, and argon was continuously introduced to exhaust the gas in the reactor. A 300 W LED lamp was turned on and the mixture was fully stirred for 1 h under illumination. After the reaction was completed, the gas product was collected and tested. The photocatalyst generated by this technical solution has a good hydrogen production effect.

[0034] Embodiment 17

[0035] 50 mg of the solid product in Examples 1 to 14 was added to a quartz tube containing 100 mL of deionized water, and carbon dioxide was introduced. A 300 W LED lamp was turned on, and the mixture was stirred for 1 h under illumination. After the reaction was completed, the gas product was collected. The photocatalyst generated by this technical solution had a good carbon dioxide reduction effect.

[0036] Embodiment 18

[0037] Cu(NO3)2·3H2O was dissolved in water to prepare 2+ In a typical adsorption experiment, 50 mg of the solid product of Examples 1 to 14 was added to 200 mL of 500 mg·L -1 The heavy metal solution was stirred at 500 rpm. The removal efficiency of heavy metals was quantified by measuring the adsorption amount at a contact time of 30 min. The adsorbed solution was centrifuged to analyze the heavy metal ion adsorption.

[0038] Embodiment 19

[0039] Cd(NO3)2·4H2O was dissolved in water to prepare 2+ In a typical adsorption experiment, 50 mg of the solid product of Examples 1 to 14 was added to 200 mL of 500 mg·L -1 The heavy metal solution was stirred at 500 rpm. The removal efficiency of heavy metals was quantified by measuring the adsorption amount at a contact time of 30 min. The adsorbed solution was centrifuged to analyze the heavy metal ion adsorption.

[0040]

Claims

1. A method for preparing porous hydrothermal carbon materials using waste plastics, characterized in that: In a closed container, waste plastics are added to a water-immiscible organic solvent and water, and an inorganic base catalyst that is insoluble or slightly soluble in water is added to form an organic-water emulsion system under the assistance of ultrasound, and further hydrothermal carbonization is performed to obtain a porous carbon material.

2. The method for preparing a porous hydrothermal carbon material according to claim 1, characterized in that: The waste plastic is selected from polyethylene terephthalate, polypropylene, polyethylene, polyvinyl chloride, polyurethane, and polystyrene.

3. The method for preparing a porous hydrothermal carbon material according to claim 1, characterized in that: The water-immiscible organic solvent is selected from cyclohexane, octane, heptane, petroleum ether, toluene, p-xylene, m-xylene, o-xylene, biphenyl, and cyclohexanone.

4. The method for preparing a porous hydrothermal carbon material according to claim 1, characterized in that: In the organic solvent-water system, the volume ratio of organic solvent to water is M , M The range is 10~500.

5. The method for preparing a porous hydrothermal carbon material according to claim 4, characterized in that: The volume ratio of waste plastic mass to organic solvent-water is R , R The range is 0.005~0.5g / mL.

6. The method for preparing a porous hydrothermal carbon material according to claim 1, characterized in that: The inorganic base catalyst is selected from Mg(OH)2, Ca(OH)2, Ba(OH)2, Sr(OH)2, CaO, MgO, BaO, SrO.

7. The method for preparing a porous hydrothermal carbon material according to claim 1, characterized in that: The organic solvent-water system containing waste plastics was ultrasonically assisted to form an emulsion, with an ultrasonic power of 200-1800 W and an ultrasonic time of 30-240 min.

8. The method for preparing a porous hydrothermal carbon material according to claim 1, characterized in that: The hydrothermal treatment reaction temperature is 160~280℃.

9. The porous hydrothermal carbon material prepared by the method according to any one of claims 1 to 8.

10. Use of the porous hydrothermal carbon material according to claim 9 in photocatalytic oxygen reduction to produce hydrogen peroxide, or water decomposition to hydrogen, or carbon dioxide reduction to produce carbon monoxide, or heavy metal ion adsorption.